Q-space analysis of scattering by small irregular particles - Sorensen, Christopher M.; Zubko, E.; Heinson, William R.; Chakrabarti, Amitabha (My University, 2014)
This paper applies the Q-space analysis method to the scattering phase function of small irregular particles. Q-space analysis involves plotting the scattered intensity versus the magnitude of the scattering wave vector q = (4π/λ) sin(θ/2) on a double log plot. Four types of irregularly shaped particles were studied: strongly damaged spheres, rough surface spheres, pocked spheres, and agglomerated debris particles. The angular scattering phase function was calculated using the discrete dipole approximation (DDA). The Q-space analysis uncovered power law descriptions of the scattering as it has previously for aggregates, spheres and dusts, although in some situations the description is marginal. It also showed that the forward scattering lobe has Rayleigh functionalities on size and refractive index. These results imply that Q-space analysis can yield a comprehensive description of scattering in terms of power laws with quantifiable exponents for a wide variety of particle shapes. However, a theoretical explanation of the power laws and the values of the numerical exponents is lacking.
Keywords: Light scattering; Q-space analysis; Phase function; Irregularly shape particles